Chiari IV Malformation, the Lückenschädel and Sagittal Craniosynostosis Association: Case Report and Literature Review - Biasi, Pedro Radalle; Roso, Laura Regyna Toffoli; Manfroi, Grégori; Espanhol, Rafael Augusto; Almeida, Timóteo Abrantes de Lacerda; Brunet, Matheus Pintos; Souza, Wellington César de; Baldissera, Eduardo Felipe Martinelli; Rech, Bruna Constantino; Posenato, Naiana; Crusius, Marcelo Ughini (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2016)
The association between Lückenschädel and craniosynostosis is unusual and unknown. Genetic origin is a possibility, representing one of many possible phenotypes for mutation. To the best of our knowledge, the association of such anomalies in a type IV Chiari malformation has never been reported before. The authors present the case of a patient with obstructive hydrocephalus, diagnosed with Chiari IV malformation associated with Lückenschädel and sagittal craniosynostosis. The Lückenschädel is the bone abnormality least commonly associated with Chiari malformation. It consists of a defect in the bones of membranous origin that form the cranial vault. This anomaly arises from periosteal dysplasia, and is characterized by rounded and irregular gaps in the skull, bound by bony ridges. Craniosynostosis is due to premature fusion of the cranial sutures and is sometimes associated with the Chiari complex of malformations. The diagnostic of Lückenschädel and craniosynostosis is done by imaging, through which the skull assumes the aspect of a hive, characteristic of Lückenschädel and it is possible to see the premature fusion of the sutures. The Lückenschädel usually does not require treatment because of spontaneous resolution; whereas, craniosynostosis warrants surgery for aesthetic and functional reasons. The Chiari malformation IV only requires treatment when it results in syringomyelia or hydrocephalus.
Keywords: Chiari malformation; Lückenschädel; craniosynostosis; hydrocephalus; ventriculostomy